The Legal Position of Sumang Child According to Customary Law in Kopong Village of East Nusa Tenggara - Evi Djuniarti (Jurnal Penelitian Hukum De Jure, 2022)
The existence of Sumang Child for the people of Kopong Village, Sikka Regency, East Nusa Tenggara is a “disgrace” for his extended family, so based on local customs, the parents as well as the child must be expelled from the village, after going through the customary procession. Children born from unexpected relationships do not have rights either from the family of the 2 (two) parents or based on the provisions of national and international law. The formulation of the problem in the writing of this paper is “How is the Position of Sumang Child seen from Customary Law and State Law? This research is secondary data obtained through literature studies in the form of laws and descriptive analysis. Custom is a very sacred ritual for the people of Kopong village, Sikka Regency, East Nusa Tenggara, especially regarding ceremonies for the existence of Sumang Child and the parents that cannot be delayed or avoided. When viewed from the existence of the Child Protection Law and other regulations, this does not occur in the protection of the child and his parents.